A modular assembly of chiral oxazolinylcarbene-rhodium complexes: efficient phosphane-free catalysts for the asymmetric hydrosilylation of dialkyl ketones - Gade, Lutz H.; César, Vincent; Bellemin-Laponnaz, Stéphane (Angewandte Chemie. International edition, 2004)
A novel class of chiral bidentate ligands with a carbene and an oxazoline moiety is obtained by the coupling of N-arylimidazoles and a 2-bromooxazoline derivative. The rhodium complex 1 catalyzes the hydrosilylation of aryl alkyl ketones and otherwise problematic dialkyl ketones in high yields and good enantioselectivities (up to 95 % ee).